2011
DOI: 10.1007/s10482-010-9546-x
|View full text |Cite
|
Sign up to set email alerts
|

The tsetse fly Glossina fuscipes fuscipes (Diptera: Glossina) harbours a surprising diversity of bacteria other than symbionts

Abstract: Three different bacterial species are regularly described from tsetse flies. However, no broad screens have been performed to investigate the existence of other bacteria in this medically and agriculturally important vector insect. Utilising both culture dependent and independent methods we show that Kenyan populations of Glossina fuscipes fuscipes harbour a surprising diversity of bacteria. Bacteria were isolated from 72% of flies with 23 different bacterial species identified. The Firmicutes phylum dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 48 publications
5
95
0
Order By: Relevance
“…It should also be noted that recent field studies have found an unexpected diversity within the microbial community of tsetse which is dependent on host species and geographic region (49,51). Differences in abiotic conditions and food sources may influence the composition of these transient microbial communities (49,94).…”
Section: Impact Of Additional Microbes On Holobiont Successmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be noted that recent field studies have found an unexpected diversity within the microbial community of tsetse which is dependent on host species and geographic region (49,51). Differences in abiotic conditions and food sources may influence the composition of these transient microbial communities (49,94).…”
Section: Impact Of Additional Microbes On Holobiont Successmentioning
confidence: 99%
“…Tsetse can also harbor the Alphaproteobacteria Wolbachia (44), a facultative parasite infecting many different invertebrates (45,46), which is typically restricted to the reproductive organs (47,48). Field studies report a more complex diversity in adult flies (49)(50)(51), although these microbes are believed to be transient in nature. The tsetse holobiont provides opportunities to examine evolutionary aspects associated with adapting to microbial coresidence, as Wigglesworthia and Sodalis have drastically different times of establishment (10,52).…”
Section: Tsetse Microbial Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…(17), the commensal Sodalis glossinidius (18), and members of the parasitic genus Wolbachia (19,20). Field studies report a more complex and diverse adult microbiota (21)(22)(23)(24), although the majority is believed to be transient in nature. Enhanced knowledge of tsetse symbioses may provide novel and specific avenues for vector control, such as through paratransgenesis, in which symbionts deliver effector molecules that interfere with parasite development (25,26), or the use of a novel class of pesticides aimed at disrupting pivotal symbiont-mediated tsetse fly metabolic processes.…”
mentioning
confidence: 99%
“…Both symbionts are vertically transmitted via milk glands (7,9,10) and are presumed to compensate for the nutritionally unbalanced blood diet (11)(12)(13)(14)(15). This highly specific microbiome of tsetse flies is usually accompanied by reproductive manipulators from the genus Wolbachia (16) and a diversity of other transient bacteria of unknown relationship to the host (17,18). In contrast to Glossinidae, the family Hippoboscidae is a species-rich, highly diversified, and cosmopolitan group feeding on mammals and birds (4).…”
mentioning
confidence: 99%